HUBUNGAN ASUPAN SERAT, LEMAK, AKTIVITAS FISIK DAN KADAR LDL PADA PASIEN PENYAKIT JANTUNG KORONER DI RSUD Dr. M. YUNUS BENGKULU TAHUN 2016 - Yusira, Puvet; Wahyuni, Yulia; Hartati, Lilik Sri (Lembaga Penerbitan Unversitas Esa Unggul, 2017)
According to the National Household Health Survey (SKRTN), heart disease is the greatest causes of mortality (about 26.4%). In Bengkulu, out of ten, cardiovascular disease is the second most prevalence disease. We aimed to examine the association of dietary fiber and fat intake and physical activity with Low Density Lipoprotein (LDL) level among coronary heart diseases (CHDs)’s patient. The study was Cross-sectional study design. Samples were 52 which taken from total sampling method. Intake nutrients were collected using 24 hours food recall. Physical activity measured physical activity level questionnaire. LDL levels in CHDs’s patient were obtained from medical records. Results showed that two variables significantly associated with LDL levels in CHDs’s patient, namely fat intake (p value =0,008) and physical activity (p value = 0,019) while fiber intake was not significantly associated with LDL levels in CHDs’s patient (p value = 0,194). Fat intake in accordance with individual needs accompanied by good physical activity can affect the value of LDL level among CHDs’s patient. Keywords: Physical Activity, Fat intake, Fiber Intake, LDL, Coronary Heart Disease